Review of the Genus Ambotingis Drake and Ruhoff (Hemiptera: Heteroptera: Tingidae) - Knudson, Alexander H.; Rider, David A.; Knodel, Janet J. (Zootaxa, 2017)
Dictyla ainsliei (Drake and Poor) is transferred to the genus Ambotingis Drake and Ruhoff, redescribed, and reported from Costa Rica for the first time. Ambotingis senta (Drake and Hambleton) is also diagnosed, and a key for the separation of the two species is provided.